A quick method of determining the age of 8 years old: Based on the first premolars on Eastern Chinese population. (November 2021) - Shen, Shihui; Guo, Yibo; Wang, Miaochen; Wang, Jian; Fan, Linfeng; Ji, Fang; Tao, Jiang
Highlights: The first premolar maturity index was proposed to determine age 8 years or older. A cutoff value of I1PM (f irst premolar maturity index) = 0.35 was taken. Abstract: Background: Whether an individual is over 8 years old is of great significance in clinical medicine and law. The Demirjian, Willems and Cameriere methods are one of the most widely used methods of dental age estimation, but neither method was suitable in Eastern China. And all of them are time-consuming for clinical work. A new and time-saving method for judging whether an individual is 8 years old is yet to be proposed on Eastern Chinese population. Aim: The paper proposes a method for judging whether an individual is 8 years old based on the relationship between age and the first premolar maturity index (I1PM ), which is related to the measurement of the open apices of the first premolar. Subjects & Methods: It is a retrospective study where orthopantomograms of 748 children (356 female and 392male) aged 5–13 years were collected and analyzed. Linear regression was used to infer the value of I1PM for eastern China. Furthermore, this method was compared to those based on Demirjian's stages F. Results and Conclusions: A cutoff value of I1PM = 0.35 was taken. The sensitivity of this test was 90.0% and specificity was 93.3%. Furthermore, the proportion of individuals with a correct classification was 90.9%. The results of the test showed that Demirjian's stage F performance was lightly better than I1pm < 0.35. However, the sensitivity, specificity, and overall accuracy of both are greater than or equal to 90.0%, and the differences are not very significant.